The Development of a Gamebird Research Strategy: Unraveling the Importance of Arthropod Populations - Nicolas W. Sotherton (National Quail Symposium Proceedings, 2017)
This paper describes work conducted in the United Kingdom (UK) on upland gamebirds, primarily gray partridge, that identified the importance of arthropod abundance in determining chick survival and in the overall population dynamics of this declining quarry species. Several sequential steps that were taken to quantify the importance of arthropods in determining levels of chick survival, ranging from laboratory studies with captive chicks, through field-based surveys to computer simulation are described. Next, various field-scale experiments to manipulate vegetation to increase arthropod densities are described. These included the management of cereal crop edges with reduced levels of pesticides.